2011
DOI: 10.1007/s00198-011-1573-6
|View full text |Cite
|
Sign up to set email alerts
|

New laboratory tools in the assessment of bone quality

Abstract: Bone quality is a complex set of intricated and interdependent factors that influence bone strength. A number of methods have emerged to measure bone quality, taking into account the organic or the mineral phase of the bone matrix, in the laboratory. Bone quality is a complex set of different factors that are interdependent. The bone matrix organization can be described at five different levels of anatomical organization: nature (organic and mineral), texture (woven or lamellar), structure (osteons in the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 106 publications
2
80
0
3
Order By: Relevance
“…The aims of the present study were to conduct a comprehensive investigation of trabecular bone mass and microarchitecture in GIPR knockout male mice and to assess other parameters of quality of the trabecular bone matrix [16]. Our results indicated that 16-week-old GIPR-deficient male mice present with a significant increase in BV/TV, associated with an increase in trabecular number and a decrease in osteoclast number.…”
Section: Introductionmentioning
confidence: 79%
“…The aims of the present study were to conduct a comprehensive investigation of trabecular bone mass and microarchitecture in GIPR knockout male mice and to assess other parameters of quality of the trabecular bone matrix [16]. Our results indicated that 16-week-old GIPR-deficient male mice present with a significant increase in BV/TV, associated with an increase in trabecular number and a decrease in osteoclast number.…”
Section: Introductionmentioning
confidence: 79%
“…However, very little information has been reported. Tissue material properties represent a set of parameters that describe the modification of biochemical composition or organisation of the bone matrix at the molecular and nanoscale levels (Chappard et al 2011). This encompasses for a thorough assessment of the mineral and collagen compartments.…”
Section: Effects Of Glp-1ras On Tissue Materials Propertiesmentioning
confidence: 99%
“…On the other hand, the organic component includes collagen fibrils (90%) and a small amount of noncollagenous proteins (Kini & Nandeesh, 2012). It confers elastic and flexible properties to the bone matrix, and strength in tension as well as the ability to absorb energy (Viguet-Carrin et al, 2006;Chappard et al, 2011;Kini & Nandeesh, 2012).…”
Section: Composition Of Bonementioning
confidence: 99%
“…The major characteristics of osteoporosis are low bone mass and microarchitectural deterioration of bone that leads to an increase in the risk of fractures in bones (Chappard et al, 2011). A low bone mass can be diagnosed by a bone mineral density (BMD) test.…”
mentioning
confidence: 99%
See 1 more Smart Citation